Tracking progress towards the Millennium Development Goals: reaching consensus on child mortality levels and trends (The World Health Organization, 2006)
The increased attention to tracking progress towards the Millennium Development Goals (MDG), including Goal 4 of reducing child mortality, has drawn attention to a number of interrelated technical, operational and political challenges and to the underlying weaknesses of country health information systems upon which reliable monitoring depends. Assessments of child mortality published in 2005, for almost all low-income countries, are based on an extrapolation of the trends observed during the 1990s, rather than on the empirical data for more recent years. The validity of the extrapolation depends on the quality and quantity of the data used, and many countries lack suitable data. In the long run, it is hoped that vital registration or sample registration systems will be established to monitor vital events in a sustainable way. However, in the short run, tracking child mortality in high-mortality countries will continue to rely on household surveys and extrapolations of historical trends. This will require more collaborative efforts both to collect data through initiatives to strengthen health information systems at the country level, and to harmonize the estimation process. The latter objective requires the continued activity of a coordinating group of international agencies and academics that aims to produce transparent estimates- through the consistent application of an agreed-upon methodology- for monitoring at the international level.